Facilitators and Barriers to Seeking Mental Health Care Among Primary Care Veterans With Posttraumatic Stress Disorder. Issue 5 (19th October 2018) - Possemato, Kyle; Wray, Laura O.; Johnson, Emily; Webster, Brad; Beehler, Gregory P.
Abstract: Although posttraumatic stress disorder (PTSD) is common in primary care patients, many do not seek mental health treatment. Existing research on barriers and facilitators to receiving PTSD treatment are not specific to primary care patients. In this study, we sought to understand the psychosocial concerns, treatment barriers, and treatment facilitators among non‐treatment‐seeking primary care veterans with PTSD who reside in both rural and urban settings. Using a concurrent triangulation design, we collected qualitative focus group and quantitative self‐report data concurrently, analyzed them separately, and merged the results for interpretation. In total, 27 veteran primary care patients with PTSD participated in 1 of 4 focus groups. A modified conventional content analysis approach was used. Team‐based coding began with three broad primary codes (psychosocial concerns, barriers, and facilitators) and subcodes were allowed to emerge from the data. Self‐report measures were used to collect clinical characteristics and barriers to care. The results expanded upon existing models of PTSD treatment initiation by (a) specifying treatment preferences, such as patient‐centered care, peer support services, and open access scheduling, and (b) presenting concerns, such as anger and core symptoms of PTSD. Results also indicated that a commonly used quantitative barriers measure may offer an incomplete picture of why veterans do not seek treatment as it does not assess how past negative treatment experiences may affect utilization. Strategies to help veterans overcome barriers to care may benefit from a focus on negative treatment‐seeking beliefs and tailoring based on a veteran's rural or urban status. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Facilitadores y barreras para la búsqueda de atención de salud mental entre veteranos de atención primaria con TEPT FACILITADORES Y BARRERAS PARA BÚSQUEDA DE ATENCIÓN EN TEPT El trastorno de estrés postraumático (TEPT) es común en pacientes de atención primaria, sin embargo no buscan un tratamiento de salud mental. Las investigaciones existentes acerca de barreras y facilitadores para recibir tratamiento en TEPT no son específicas en pacientes de atención primaria. En este estudio, hemos buscado entender las preocupaciones psicosociales, barreras y facilitadores de tratamiento entre veteranos que no buscan tratamiento de atención primaria en TEPT que residen en ambos contextos urbano y rural. Utilizando un diseño de triangulación concurrente, recolectamos datos cualitativos a través de grupos focales y cuantitativos a través de autoreportes, de manera simultánea, analizándolos de manera separada, y fusionando los resultados para su interpretación. En total 27 pacientes veteranos de atención primaria con TEPT participaron en uno de cuatro grupos focales. Se utilizó un enfoque de análisis de contenido convencional modificado. La codificación realizada en el equipo comenzó con tres amplios códigos primarios (preocupaciones psicosociales, barreras y facilitadores) y se permitió la aparición de subcódigos a partir de los datos. Las medidas de autoreportes se usaron para recopilar las características clínicas y las barreras para la atención. Los resultados amplían los modelos existentes de iniciación del tratamiento de TEPT al (a) especificar preferencias de tratamiento, tales como atención centrada en el paciente, servicios de apoyo entre pares y programación de acceso abierto, y (b) presentar preocupaciones, como enojo y síntomas centrales de TEPT. Los resultados también indican que un uso común de medir barreras cuantitativamente puede ofrecer una imagen incompleta de por qué los veteranos no buscan tratamiento, ya que no evalúa cómo las experiencias pasadas de tratamiento negativo pueden afectar la utilización. Las estrategias para ayudar a los veteranos a superar las barreras para la atención pueden beneficiarse de un enfoque en las creencias negativas sobre la búsqueda de tratamiento y la adaptación en función del contexto rural o urbano de un veterano. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Facilitators and Barriers to Seeking Mental Health Care among Primary Care Veterans with PTSD Traditional Chinese 標題: 接受初級醫療並患PTSD的退役軍人尋求心理治療的促進因素和障礙 撮要: 創傷後壓力症(PTSD)在接受初級醫療的患者中普遍, 但很多患者都不尋求心理治療。現有對於接受PTSD治療的障礙和促進因素研究, 並未特殊地檢視初級醫療患者的個案。本研究透過居於郊區和市區、接受初級醫療、患PTSD但未有尋求心理治療的退役軍人, 檢視心理社會因素、尋求治療的障礙和促進因素。我們採用同步三角驗證的模型設計, 同時收集了針對組的質性數據和自評的量化數據, 對其分開分析, 再結合結果進行詮釋。共有4個針對組和27名接受初級醫療的PTSD退役軍人參與在內。我們採用經過修改的傳統式內容分析法, 在3種廣泛的初級編碼 (心理社會因素、尋求治療的障礙和促進因素) 開始進行組別為本的編碼, 亦從數據中得出副編碼。自評測量用以收集臨床特徵和尋求治療的障礙數據。是次研究擴闊了現有對開始PTSD治療的研究模型, 因為(a)特殊地檢視治療偏好, 如以患者為中心的治療、朋輩支援計劃、開放預約;及(b)關注到如憤怒和PTSD核心症狀等因素。結果亦反映, 普遍用到的量化障礙測量並未能評估過往的負面治療經歷如何影響治療使用率, 用於研究退役軍人為何不尋求治療, 得出的結果可能不夠全面。幫助退役軍人克服治療障礙的策略, 包括針對改善他們對尋求治療的負面想法, 並因應退役軍人居於郊區或市區而調校治療服務。 Simplified Chinese 标题: 接受初级医疗并患PTSD的退役军人寻求心理治疗的促进因素和障碍 撮要: 创伤后压力症(PTSD)在接受初级医疗的患者中普遍, 但很多患者都不寻求心理治疗。现有对于接受PTSD治疗的障碍和促进因素研究, 并未特殊地检视初级医疗患者的个案。本研究透过居于郊区和市区、接受初级医疗、患PTSD但未有寻求心理治疗的退役军人, 检视心理社会因素、寻求治疗的障碍和促进因素。我们采用同步三角验证的模型设计, 同时收集了针对组的质性数据和自评的量化数据, 对其分开分析, 再结合结果进行诠释。共有4个针对组和27名接受初级医疗的PTSD退役军人参与在内。我们采用经过修改的传统式内容分析法, 在3种广泛的初级编码 (心理社会因素、寻求治疗的障碍和促进因素) 开始进行组别为本的编码, 亦从数据中得出副编码。自评测量用以收集临床特征和寻求治疗的障碍数据。是次研究扩阔了现有对开始PTSD治疗的研究模型, 因为(a)特殊地检视治疗偏好, 如以患者为中心的治疗、朋辈支持计划、开放预约;及(b)关注到如愤怒和PTSD核心症状等因素。结果亦反映, 普遍用到的量化障碍测量并未能评估过往的负面治疗经历如何影响治疗使用率, 用于研究退役军人为何不寻求治疗, 得出的结果可能不够全面。帮助退役军人克服治疗障碍的策略, 包括针对改善他们对寻求治疗的负面想法, 并因应退役军人居于郊区或市区而调校治疗服务。